Give and take? Knowledge exchange between older and younger employees as a function of generativity and development striving. Issue 10 (12th November 2021) - Fasbender, Ulrike; Gerpott, Fabiola H.; Unger, Dana
Abstract : Purpose: Knowledge exchange between older and younger employees enhances the collective memory of an organization and therefore contributes to its business success. The purpose of this paper is to take a motivational perspective to better understand why older and younger employees share and receive knowledge with and from each other. Specifically, this study focuses on generativity striving – the motivation to teach, train and guide others – as well as development striving – the motivation to grow, increase competence and master something new – and argues that both motives need to be considered to fully understand intergenerational knowledge exchange. Design/methodology/approach: This paper takes a dyadic approach to disentangle how older employees' knowledge sharing is linked to their younger colleagues' knowledge receiving and vice versa. The study applied an actor-partner interdependence model based on survey data from 145 age-diverse coworker dyads to test the hypotheses. Findings: Results showed that older and younger employees' generativity striving affected their knowledge sharing, which, in turn, predicted their colleagues' knowledge receiving. Moreover, the study found that younger employees were more likely to receive knowledge that their older colleagues shared with them when they scored higher (vs lower) on development striving. Originality/value: By studying the age-specific dyadic cross-over between knowledge sharing and knowledge receiving, this research adds to the knowledge exchange literature. This study challenges the current age-blind view on knowledge exchange motivation and provides novel insights into the interplay of motivational forces involved in knowledge exchange between older and younger employees.